Compensation and Career Development on Employee Retention: A Review of the Literature - Azis Rachman; Aslan Hamzah (Westscience Press, 2023)
This study aims to determine the effect of compensation and career development on employee retention. The writing method uses review literature articles with data sources coming from various platforms such as Google Scholar, Mendeley, Semantic Scholar, and other online academic sources. The results of the study are compensation has a positive and significant effect on employee retention, career development has a positive and significant effect on employee retention.